The value and life of products and services based on culture, knowledge, and technology - Gaytán Cortés, Juan (Mercados y Negocios, 2026)
Success in business management, particularly in a globalized environment, depends to a large extent on a comprehensive understanding of the relationship between the philosophy of life, the business idea, strategic planning, and the business plan, in close connection with culture, knowledge, and technology. This interrelationship constitutes an essential framework of reference for business decision-making aimed at creating sustainable value.